"Terrorist Design" of the Russian Federation in the Destruction of Churches in Ukraine from 2014 to 2023 - Bulatov, Valeriy (Occasional papers on religion in Eastern Europe, 2023)
The article highlights issues related to the justification by the Russian Federation for the destruction of places of worship on the territory of Ukraine since the beginning of the war in 2014. The ongoing war in Ukraine, which began with the annexation of eastern Ukraine and Crimea in 2014, has continued with a full-scale invasion of Russian troops into Ukraine. The proclamation by the President of Russia, Putin, regarding "Russian freedom" was presented in its entirety in the destruction of the civilian population of Ukraine, including children, the elderly, and pregnant women, which is being carried out to this day in different cities. The ideological factor of the Russian invaders aims at the systematic destruction of religious buildings in Ukraine. The formation of a new regime in the occupied territories is determined by the strict control of the population to prohibit the profession of any religion, except for one permitted by the occupiers in the form of the Orthodox Church of the Moscow Patriarchate, which, in the person of Patriarch Kirill, officially blessed the seizure of the sovereign territory of Ukraine and the destruction of its people. Therefore, the incessant process of stigmatization and marginalization of people in the occupied territories is intensified by the demonstrative destruction of places of worship in Ukraine, which have cultural and spiritual value for its inhabitants. Intolerance towards the spiritual values of the inhabitants of Ukraine and their desire for freedom is expressed by the occupiers of the Russian Federation in their program of destroying the identity of the Ukrainian people and their culture. The introduction of a new concept in the occupied territories of Ukraine brings with it clearly defined signs of fascism, leading the conquered peoples into slavery, which the Putin regime is trying to present to the world community as the "Russian world."